Increasing adolescents' physical activity levels through a comprehensive school-based physical activity program: study protocol of the cluster randomized controlled trial Active School - Marion Gasser; Andrea-Maria Nadenbousch; Fabienne Egger; Mario Kamer; Stefan Valkanover; Mirko Schmidt (BMC, 2024)
Abstract Background The positive effects of regular physical activity on children and adolescents' physical and mental health are well-established. Despite these health benefits, most Swiss adolescents do not meet WHO's recommended level of physical activity, which includes a daily minimum of 60 min of moderate-to-vigorous physical activity. Due to their inclusivity, schools are identified as a key setting to promote physical activity. Recently, the comprehensive school physical activity program (CSPAP), in which teachers as physical activity leaders (PALs) play a crucial role to advance comprehensive school-based physical activity promotion, has been discussed. However, such comprehensive approaches are still lacking in Switzerland, and specific PAL trainings do not exist. Therefore, the aim of this study is to implement and evaluate Active School, a comprehensive school-based physical activity program for Swiss secondary schools with integrated PAL training. Methods/design A cluster randomized controlled trial (RCT) involving 12 secondary schools (6 experimental, 6 waiting control schools) will assess baseline data and effectiveness of Active School at 12 and 24 months. Active School includes five components based on the CSPAP. Each school is encouraged to set individual physical activity goals in this regard. This process is guided by the PALs, who will participate in professional development training before and during Active School implementation. As a primary outcome, students' moderate-to-vigorous physical activity will be assessed via accelerometers. As secondary outcomes, inactivity, light physical activity, step counts, aerobic fitness and coordination will be measured, and students' general wellbeing, learning behavior, and multiple psychosocial measures related to physical activity will be assessed by questionnaires. The effectiveness evaluation is accompanied by a process evaluation that focuses on the implementation outcomes of dose of delivery, reach, feasibility, and sustainability. A mixed methods approach, including ripple effect mapping, will be employed to reconstruct and understand the implementation process. Discussion This study will be the first to implement and evaluate a CSPAP in the Swiss school system. The specific PAL training and the simultaneous application of effectiveness and process evaluation are considered strengths of the study. Trial registration German Clinical Trials Register (DRKS00033362). Date of registration: January 25, 2024. Retrospectively registered.